Gender and Environmental Preservation - Nzeyo Gabriel Eteng; Adams Peter Akpo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2022)
The paper titled gender and environmental preservation explores the nature of gender in relationship with the environment using the Yakur society in Cross River State, Nigeria as a case study, African societies generally see the world to a greater extent as a man’s world in the sense that the land and everything within the environment is owned and controlled by men. However the research discovered that women give greater priority to protection of and improving the capacity of nature by maintaining the economic/agricultural environment, political environment, spiritual environment, domestic environment and the social environment respectively. Women play critical roles in managing natural resources and the family. Secondly the paper discussed the nature of gender inequality in Yakurr societies and its impact on women. The paper adopted the historical and phenomenological methods of data collection. The qualitative method was used to analyze the data collected. The paper calls for an equal distribution of resources irrespective of gender or sex.